The un-appropriable and the mixing: on the Anthropocene and migrations - Salottolo, Delio (Itinerari, 2023)
This essay aims at analysing the relationship between the Anthropocene as fashionable concept and the migrant issue as the return of the repressed in the self-absolving Western narrative. First of all, we will deconstruct the mainstream concept of Anthropocene (starting from a well-known essay by W. Steffen, J. Grinevald, P. Crutzen and J. McNeill), showing its disquieting continuity with the conceptual and political devices of Western modernity; then, we will analyse the migrant issue, starting from the problematization of climate refugee and Achille Mbembe’s conceptualization about the becoming-Negro of the world. Secondly, we will address the concept of un-appropriable (Mbembe and Agamben): the thesis is that the Negro (in its wider meaning) can become the subject of emancipation starting from new perspectives of “use” beyond capitalist property and appropriation. Thirdly, we will show how the un-appropriable needs a new realism starting from a renewed cosmology and an ontology of mixing (Margulis and Coccia). The conclusions will investigate the implications between the two fundamental political questions: how is to be? and what is to be done?